ANALISA KESALAHAN MAHASISWA DALAM MENGGUNAKAN MORFEM PADA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FKIP UMSU - HALIMAH TUSSA’DIAH; Tengku Winona Emelia (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research aims at finding the students’ error in analyzing morfem. By applying descriptive qualitative quantitative method, the researcher analyzed the errors made by tke V semester students of English Education Program of Faculty of Teacher Training and Education UMSU Medan of the academic year 2016/2017. Totally there were 394 students as the population and 40 students or 10 % were randomly taken as the sample who would be given a test in the form of multiple choice test with 4 options in each test number (according to supervisial basis ; addition, omission, substituition and ordering). The result of the test showed that submission was the highest error ; 263 or 66% error and the lowest one was ordering ; 245 error or 61 % of the total sample. Grammatical morfem was the dominan error ; 142 error or 14 % of all kinds of morfem.